Multiligament knee injury patients with limited access to post‐operative rehabilitation exhibit similar patient‐reported outcomes: A retrospective cohort study - Shane S. Korber; Amir Fathi; Ioanna K. Bolia; Cailan L. Feingold; Eric H. Lin; Samantha A. Solaru; Neilen Benvegnu; Joseph N. Liu; George F. Rick Hatch 3rd (Journal of Experimental Orthopaedics)
Abstract Purpose Multiligament knee injuries (MLKI) are typically high‐energy traumatic injuries requiring surgical reconstruction and extensive post‐operative rehabilitation. This study aimed to examine differences in outcomes of patients with different access to post‐operative rehabilitation following multiligament knee reconstruction (MLKR). We hypothesize that patients with limited access to rehabilitation will demonstrate worse outcomes. Methods Patients who sustained an MLKI between 2007 and 2019 and who underwent MLKR by a single surgeon were retrospectively identified and invited to participate. Patients less than 1 year post‐operative were excluded. Data recorded included patient demographics, intraoperative procedure performed, patient access to rehabilitation after surgery (limited versus full access), and multiple post‐operative patient‐reported outcome measures (PROMs). A comparison of PROMs was performed between patients with limited versus full access to rehabilitation using descriptive statistics (STATA). The level of statistical significance was set at p < 0.05. Results Eighty‐three patients (17.4% female) met the inclusion criteria and had accessible rehabilitation data. Of those, 69 (83.1%) patients had full access to rehabilitation, and 14 patients (16.9%) had limited access to post‐operative rehabilitation. There was no difference in mean follow‐up time (2.6 and 2.2 years, respectively, p = 0.96) or baseline patient characteristics. Patients with limited access to post‐operative rehabilitation had significantly worse Patient‐Reported Outcome Measurement Information System (PROMIS) Pain (p = 0.021) and PROMIS Physical Function (p = 0.023) scores compared to patients with full access to rehabilitation. PROMIS mobility, Lysholm and multiligament quality of life (MLQOL) measures were not significantly different. Conclusion Patients who underwent MLKI reconstruction with limited access to rehabilitation demonstrated worse PROMIS pain and physical function scores than those with full access to rehabilitation in the short term. However, these differences do not meet minimum clinically important difference values, suggesting similar outcomes. Other PROMs, such as PROMIS mobility, Lysholm and MLQOL scores, were similar between patients with and without full access to rehabilitation. Level of Evidence Level III, retrospective cohort study.